Pendayagunaan Dana Zakat Dalam Rangka Pemberdayaan Ekonomi Mustahik Studi Lazismu Kabupaten Malang - Rahmad Hakim; Muslikhati Muslikhati; Mochamad Novi Rifa'i (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
This study aims to determine the Effectiveness of Zakat Utilization on Mustahik Economic Empowerment at Amil Zakat, Infak and Shodaqoh Muhammadiyah Institutions (LAZISMU) Malang Regency. To achieve the objectives of this research, a quantitative descriptive approach is used. Data collection methods used are various data collection methods, including: interview and documentation methods, and data analysis used content analysis. Based on the result found that found that the utilization of zakat funds at LAZISMU Malang Regency was able to increase the economic empowerment of mustahik based on several indicators: the usefulness of a program, accuracy and objectivity, the scope of a program, cost effectiveness, timeliness, and accountability. While in the aspect of timeliness of reporting, the financial reporting of zakat funds is seems not up to date.